PENGEMBANGAN PROFESIONAL GURU BERKELANJUTAN MELALUI PELATIHAN PENULISAN ARTIKEL ILMIAH BIDANG LINGKUNGAN HIDUP BERBASIS KOMPETENSI DI JAKARTA - Dwi Atmanto; Sitti Nursetiawati; Neneng Siti Silfi Ambarwati; Esti Suntari (Jurnal Bakti Masyarakat Indonesia, 2021)
Teachers are obliged to carry out tasks other than education and teaching, such as making scientific works. However, due to the limitations of teachers in terms of time, cost and competence in mastering problems and technical writing, the number of scientific works produced by teachers is minimal. This has an impact on the length of time teachers take care of promotions/positions, which is also experienced by teachers at SMPN 270 Jakarta.This training aims to provide knowledge and competence concerning to the work of teacher professional development, especially the ability to write articles based on environmental studies. Environmental competence is the mastery of the components of the social environment, the built environment and the physical environment thatare developing and integrated in each teacher's field of study. The target of the service is the teachers of SMP 270 Jakarta in all fields of study related to environmental problems. There are 32 teachers who participate in PKM activities. Problems are solved in three steps of activity, they are (1) material preparation, (2) implementation and(3) evaluation. Preparation is done by conducting a preliminary survey to see conditions in the field. The mplementation is using the lecture method (presentation), followed by discussions, questions and answers, and exercises as a form of article writing workshop activities. Evaluation is carried out for each stage by collecting andconcluding data from each stage. Collecting evaluation data through filling out questionnaires and interviews with participants. The results of the PKM activity show that there is an increase in knowledge of the concept of making scientific journal articles in the environmental field (62%) and the results of competence in one week there are 30 (90%) successfully collecting articles, although there are 24 articles (80%) articles are not perfect and must beimproved by the author.ABSTRAK:Guru sebagai profesi yang wajib melakukan tugas selain pendidikan dan pengajaran, juga pembuatan karya ilmiah baik penelitian maupun penulisan artikel. Namun keterbatasan guru baik waktu, biaya maupun kompetensi penguasaan permasalahan dan teknis penulisan, maka jumlah karya ilmiah yang dihasilkan guru sangat minim. Hal ini berdampak pada lamanya guru mengurus kenaikan pangkat/jabatan, yang juga dialami oleh guru-guru SMPN 270 Jakarta. Pelatihan yang diberikan pada masyarakat ini dimaksudkan memberi keterampilan dan kompetensi tentang penulisan ilmiah bagi profesionalitas pendidik, terutama kemampuan pembuatan artikel yang berbasis pada kajian lingkungan hidup. Kompetensi lingkungan adalah penguasaan komponen lingkungan sosial, lingkungan binaan dan lingkungan fisik yang sedang berkembang dan diintegrasikan pada bidang studi guru. Sasaran pengabdian adalah guru-guru SMP 270 Jakarta semua bidang studi yang terkait dengan permasalahan lingkungan. Ada 32 guru yang mengikuti kegiatan PKM. Ada tiga tahapan untuk mencari solusi masalah yaitu (1) Mengadakan materi, (2) orientasi pelatihan, dan (3) monitoring penilaian. Pengadaan materi merupakan langkah persiapan. Materi didapat melaui survey kebutuhan pendidik.Kegiatan pelatihan berisi simulasi dan workshop tata cara penulisan karya ilmiah. Diskusi antar tim dan antar-guru untuk memperoleh wawasan materi lingkungan hidup yang berkembang dan menjadi tema penulisan. Pengambilan data evaluasi melalui pengisian kuesioner danwawancara kepada peserta. Hasil kegiatan PKM menunjukkan bahwa terjadi peningkatan pengetahuan konsep pembuatan artikel jurnal ilmiah bidang lingkungan hidup (62%) dan hasil kompetensi dalam satu minggu ada 30 (90%) berhasil mengumpulkan artikel, meskipun ada 24 artikel (80%) belum sempurna dan harus diperbaiki oleh penulis.